Decoding the decade: Analyzing the evolution of technical and tactical performance in elite padel tennis (2011-2021) - Ungureanu, A. N.; Lupo, C.; Contardo, M.; Brustio, P. R. (International Journal of Sports Science & Coaching, 2024)
Despite the recent popularity of padel tennis and extensive scientific research on technical and tactical performance, anthropometric, biomechanical, and physiological characteristics, there is still a lack of long-term retrospective investigation. Therefore, this study aimed to analyze key performance indicators (KPIs) to provide the changes in these indicators over a decade spanning from 2011 to 2021. The sample included 45 (i.e. 100 sets; 957 games; 5743 points; and 54,918 shots) professional men's matches (Padel Pro Tour and World Padel Tour finals and semifinals) from three different sports seasons (2011, 2016, and 2021). KPIs related to time motion and technical and tactical analysis (i.e. unforced errors and winner shots) were examined. A series of linear mixed models was performed to investigate difference among competition years (2011, 2016, and 2021). Comparing the evolution of the game across the observed decade, it emerged a more progressive intense game (more explosive and rapid playing actions), decreasing number of shots per point (8.8 vs 9.5), and an increasing number of shots per minute (44.2 vs 40.0). Further, an increase in the importance of efficiency in overhead shots (unforced errors from bandeja/vibora +116% from 2011 to 2016) and responding to serve shots (unforced errors from serve return +17% from 2011 to 2021) emerged. Therefore, the present findings are able to highlight the evolution playing of professional padel (i.e. fewer shots per point, shorter effective playing time, decreased average point durations, higher number of shots per minute), thus providing references to potential valuable training plans.